Characteristics of fatigue in Parkinson’s disease: A longitudinal cohort study - Zhou, Xiaoxia; Xiang, Yaqin; Song, Tingwei; Zhao, Yuwen; Pan, Hongxu; Xu, Qian; Chen, Yase; Sun, Qiying; Wu, Xinyin; Yan, Xinxiang; Guo, Jifeng; Tang, Beisha; et al. (Frontiers in Aging Neuroscience, 2023)
Objective To assess the prevalence, evolution, clinical characteristics, correlates and predictors of fatigue as well as to investigate the influence of comorbid fatigue on the longitudinal changes in motor and non-motor symptoms over a 2-year longitudinal follow-up period in a large cohort of patients with Parkinson’s disease (PD). Materials and methods A total of 2,100 PD patients were enrolled from the Parkinson’s Disease & Movement Disorders Multicenter Database and Collaborative Network in China (PD-MDCNC), and their motor and non-motor symptoms were assessed biennially using comprehensive scales, including the 16-item Parkinson Fatigue Scale (PFS-16). Each PD patient was categorized as PD with or without fatigue on the basis of a cut-off mean PFS-16 score of 3.3. Results The prevalence of fatigue in our cohort was 36.8%. Compared to PD patients without fatigue, PD patients with fatigue were more likely to be older, have a longer disease duration, and higher baseline levodopa equivalent daily dose (all p < 0.05). Moreover, PD patients with fatigue showed more severe motor and non-motor phenotypes than those without fatigue. Overall, high total Unified Parkinson’s Disease Rating Scale (UPDRS) score (odds ratio [OR] = 1.016, 95% confidence interval [CI]: 1.009–1.024), Non-Motor Symptoms Scale score (OR = 1.022, 95% CI: 1.015–1.029), postural instability and gait difficulty (PIGD) subtype (OR = 1.586, 95% CI: 1.211–2.079), presence of excessive daytime sleepiness (EDS; OR = 1.343, 95% CI: 1.083–1.666), and wearing-off (OR = 1.282, 95% CI: 1.023–1.607) were significantly associated with fatigue in PD patients (all p < 0.05). High total UPDRS score at baseline (OR = 1.014, 95% CI: 1.002–1.027, p = 0.028) increased the risk of developing fatigue during follow-up. Although significant, the odds ratios were low and confidence intervals were narrow. Analysis of disease progression showed significant group differences in motor and non-motor symptoms. In comparison with the never-fatigue group, the persistent-fatigue group showed significantly greater progression in motor, autonomic dysfunction, sleep, depression and cognitive symptoms (all p < 0.05). Conclusion Increased disease severity, presence of the PIGD subtype, EDS, and wearing-off were associated with fatigue in PD patients. Significant subgroup-level differences were observed in the progression of motor and non-motor symptoms across different fatigue subgroups of PD patients.